1982
DOI: 10.1161/01.cir.65.7.1465
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of exercise ECG lead systems in clinical subsets of women.

Abstract: The diagnostic accuracy of 14-lead exercise electrocardiography was evaluated in 112 women who had no history of myocardial infarction and underwent coronary angiography. The sensitivity of ST-segment displacement of 0.1 mV or more in any of 14 ECG leads was 0.79 for coronary artery stenosis of at least 70%; the specificity was 0.66. Results were similar using bipolar ECG leads CC5 and CM5 or 11 standard ECG leads. The ST-segment shifts that occurred only during exercise were associated with a 77% false-positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0
2

Year Published

1998
1998
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(17 citation statements)
references
References 49 publications
3
12
0
2
Order By: Relevance
“…18 The false-positive rate in women depends on disease prevalence and ranges from 25% in patients with typical angina to 50% in patients with atypical chest pain. 19 Several mechanisms have been suggested to explain the high false-positive rate of ST-segment depression in women, including the fact that estrogen has a chemical structure similar to digitalis. It has been suggested that this may be partially responsible for the high prevalence of false-positive test results in women.…”
Section: Discussionmentioning
confidence: 99%
“…18 The false-positive rate in women depends on disease prevalence and ranges from 25% in patients with typical angina to 50% in patients with atypical chest pain. 19 Several mechanisms have been suggested to explain the high false-positive rate of ST-segment depression in women, including the fact that estrogen has a chemical structure similar to digitalis. It has been suggested that this may be partially responsible for the high prevalence of false-positive test results in women.…”
Section: Discussionmentioning
confidence: 99%
“…Segmental ST depression occurred during exercise in 8 of 29 boys with ''monogenic'' familial hyperlipoproteinemia compared to 4 of 55 normal boys (p < 0.05) and in 6 of 32 hypercholesterolemic girls compared to 7 of 48 normal girls (p > 0.05). As the authors indicate, the clinical importance of these findings is not clear in light of the known occurrence of false positives in adults and the higher prevalence of false positives in adult females [16]. They report that the findings were reproducible on follow-up exercise testing in both the hyperlipidemic and normal children.…”
Section: Exercise Testing In Children With Abnormal Lipidsmentioning
confidence: 97%
“…What has been established is that women with typical symptoms of angina and obvious changes in their ECG at rest and after exercise tests do not display atherosclerotic changes in the coronary arteries to the same extent as men, at least not in the epicardial vessels which appear in coronary angiography [33,34] .…”
Section: Symptomatologymentioning
confidence: 99%
“…Studies [33][34][35][36][37] have shown that women with typical angina have a high prevalence of coronary artery disease, whereas the prevalence among those with atypical symptoms was low. Once again, however, age is significant, as pre-menopausal women with typical angina manifest a prevalence of 50% as opposed to 90% in older women with the same symptoms.…”
Section: Diagnosticsmentioning
confidence: 99%